Inorganic pollutants in water - Devi, Pooja; Singh, Pardeep; Kansal, Sushil Kumar (Elsevier, 2020)
Inorganic Pollutants in Water provides a clear understanding of inorganic pollutants and the challenges they cause in aquatic environments. The book explores the point of source, how they enter water, the effects they have, and their eventual detection and removal. Through a series of case studies, the authors explore the success of the detection and removal techniques they have developed. Users will find this to be a single platform of information on inorganic pollutants that is ideal for researchers, engineers and technologists working in the fields of environmental science, environmental engineering and chemical engineering/ sustainability. Through this text, the authors introduce new researchers to the problem of inorganic contaminants in water, while also presenting the current state-of-the-art in terms of research and technologies to tackle this problem. --